Pengembangan E-LKPD Berbasis Liveworksheet pada Mata Pelajaran IPAS Kelas IV Sekolah Dasar - Hilda Eka Putri; Yeni Erita (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research focused on creating a Liveworksheet E-LKPD for fourth-grade Natural and Social Sciences to address the lack of technology-integrated learning resources. The development followed the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Validation by experts in content, language, and media yielded scores of 92%, 97%, and 90%, respectively—classified as highly valid. Practicality assessments across several trial schools also produced excellent results (95,65%, 97.96%, and 96.43%), as did the effectiveness evaluations (95.23%, 93.75%, and 95.00%). Consequently, the E-LKPD is considered highly appropriate for use in the classroom